2020
DOI: 10.3390/metabo10110475
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Adipogenic Effect of Theabrownin Is Mediated by Bile Acid Alternative Synthesis via Gut Microbiota Remodeling

Abstract: Theabrownin is one of the most bioactive compounds in Pu-erh tea. Our previous study revealed that the hypocholesterolemic effect of theabrownin was mediated by the modulation of bile salt hydrolase (BSH)-enriched gut microbiota and bile acid metabolism. In this study, we demonstrated that theabrownin ameliorated high-fat-diet (HFD)-induced obesity by modifying gut microbiota, especially those with 7α-dehydroxylation on the species level, and these changed microbes were positively correlated with secondary bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Secondary BAs can be resorbed to the portal circulation and are transported to the liver, where, however, hydroxylation and conjugation needs to be restored for reuse. The main secondary BAs in humans are lithocholic acid (LCA), deoxycholic acid (DCA) and to a lesser extent, ursodeoxycholic acid (UDCA) [ 24 , 25 ].…”
Section: Bacterial Metabolism Of Bile Acids Production Of Secondary B...mentioning
confidence: 99%
“…Secondary BAs can be resorbed to the portal circulation and are transported to the liver, where, however, hydroxylation and conjugation needs to be restored for reuse. The main secondary BAs in humans are lithocholic acid (LCA), deoxycholic acid (DCA) and to a lesser extent, ursodeoxycholic acid (UDCA) [ 24 , 25 ].…”
Section: Bacterial Metabolism Of Bile Acids Production Of Secondary B...mentioning
confidence: 99%
“…27 Its medical activities include inducing significant weight loss, lowering blood lipid and blood glucose levels, regulating intestinal microorganisms, 28 and improving the metabolic syndrome. 29 Although TB has a preventive effect on hyperglycemia in rats that are fed a high-glucose and high-fat diet, 30 the direct impact of TB on the treatment of diabetes and its mechanism of action are still unclear. In particular, the interaction between TB and intestinal microorganisms and whether TB has a targeted regulation need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of TB + PCP on reducing lipid has not been explained although previous studies revealed that TB and PCP could alleviate hyperlipidemia through several mechanisms ( Huang et al, 2019a ; Huang et al, 2019b ; Kim et al, 2019 ; Kuang et al, 2020 ). In the current study, the combination of TB and PCP was found to significantly reduce body weight, adipose tissue weight, and lipid levels (e.g., TG, TC, and LDL in the liver).…”
Section: Discussionmentioning
confidence: 99%
“…Theabrownin (TB) is a kind of water-soluble polyphenols produced through pu-erh tea fermentation ( Huang et al, 2019a ; Kuang et al, 2020 ). Our previous study has proved that after TB treatment, the body weight, blood and liver lipid levels are reduced in humans and mice ( Huang et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation